Sukuk vs. Eurobonds : Is There a Difference in Value-at-Risk? - Raei, Faezeh (IMF Working Papers; Working Paper ;, 2007)
This paper assesses the impact of bonds issued according to Islamic principles (Sukuk), on the cost and risk structure of investment portfolios by using the Value-at-Risk (VaR) framework. The market for Sukuk has grown tremendously in recent years at about 45 percent a year. Sukuk provide sovereign governments and corporations with access to the huge and growing Islamic liquidity pool, in addition to the conventional investor base. The paper analyzes whether secondary market behavior of Eurobonds and Sukuk issued by the same issuer are significantly different to provide gains from diversification. The analysis, employing the delta-normal as well as Monte-Carlo simulation methods, implies such gains are present and in certain cases very significant.